Analisis Gangguan Delusi pada Remaja Generasi Z yang Mengalami Obsesi di Desa Cigedog Kecamatan Kersana Kabupaten Brebes - Wati, Rahma Ambar; Sucipto, M. Arif Budiman; Mulyani, Mulyani Mulyani (Jurnal Empati Bimbingan dan Konseling, 2025)
Generation Z relies heavily on the internet and social media, making them have instant desires and are obsessed with their dreams. This causes them to experience delusional disorders. The purpose of this study is to determine the types, causative factors and impacts of delusional disorders experienced by Generation Z adolescents who experience obsession. This study is a qualitative study. The source of research data uses primary and secondary data, the form of data in the form of words and pictures, not emphasizing numbers. Data collection techniques use observation, interviews, documentation, triangulation. Data analysis uses qualitative descriptive analysis. The results of the study show the types of delusional disorders experienced by Generation Z adolescents who experience obsession, namely the type of delusion with the grandiose type (SRP and AW), while AA with the erotomanic type. The factors that cause delusional disorders are generally due to environmental and psychological factors. The impact of delusional disorders generally has an impact on stress and depression, social isolation and self-harm. Patients with delusional disorders generally become alienated from others, especially if their delusions interfere with their social ties.Keywords: delusions, teenagers, generation Z and obsession